A Review on Solid Carbon Formation from CO2 - Jitendra Singh Chouhan,; Rishabh Mishra,; Taneja, Ankit Kumar; Rohit Sharma, (International Journal of Psychosocial Rehabilitation, 2020)
The need to stop the emissions of greenhouse gases are needed more than ever now. Carbon emissions are one of the biggest contributing factors to the increasing global warming, pollution and climate change in the world. The Carbon emissions led to an increased amount of Carbon Dioxide in the atmosphere, and it gets trapped in the ozone layer, resulting in less protection from UV rays and Solar Radiation. This paper examines the method of Carbon capture and utilization, reducing anthropogenic emissions and providing us with the all- important, Carbon Fiber. Carbon Fiber, a very strong material known for its high tensile strength, low weight to strength ratio, low thermal expansion etc. which makes it an ideal material for the manufacturing industry. Traditionally, Carbon Fibers were manufactured using petroleum-based materials, but advancements in technology have made it feasible to produce carbon fibers from alternative carbon sources, including captured carbon dioxide (CO2).